Artificial Intelligence in Education: Opportunities and Challenges in the Transition from Industry 4.0 to Society 5.0 - Putra, Indra Pratama; Muhammad Adri; Dedy Irfan (Universitas Negeri Padang, 2025)
The integration of Artificial Intelligence (AI) into education has become increasingly relevant in the era of Industry 4.0 and the transition toward Society 5.0. This study aims to provide a bibliometric analysis of research trends, thematic clusters, and emerging keywords related to AI in education between 2018 and 2025. Using the Publish or Perish software and data from Google Scholar, 200 articles were selected based on relevance and citation metrics. Keyword co-occurrence analysis and visual mapping were conducted using VOSviewer to identify dominant research themes. The results reveal a growing body of literature focused on AI applications in education, with key topics including adaptive learning, machine learning, digital transformation, and human-centered innovation. However, critical gaps remain, particularly in research addressing cultural context, teacher readiness, digital equity, and the long-term impact of AI-driven tools. This study highlights the need for inclusive, ethical, and context-aware approaches to AI in education, offering insights and recommendations for future research aligned with the human-centric values of Society 5.0